Effects of mu, kappa, and delta opioid receptor agonists and antagonists on rat hypothalamic noradrenergic neurotransmission - Yilmaz, B; Gilmore, DP (Pergamon-Elsevier Science Ltd, 1999)
We have investigated the effects of specific mu-, kappa- and delta-opioid receptor agonists and antagonists on the hypothalamic noradrenergic neurotransmission and on luteinising hormone (LH) release in the ovariectomised and steroid-primed rat. The opioid agents were infused intracerebroventricularly under ketamine anaesthesia and blood samples collected at hourly intervals on the afternoon of the anticipated LH surge. At the end of the experiment, the rats were decapitated and the medial preoptic area, suprachiasmatic nucleus, median eminence and arcuate nucleus surgically isolated by micropunch. The concentrations of noradrenaline (NA) and its metabolite (3,4-dihydroxyphenylglycol; DHPG) in these samples was determined by high performance liquid chromatography with electrochemical detection, Plasma LH levels were measured by radioimmunassay, The three opioid agonists reduced concentrations of NA and DHPG in all four hypothalamic areas. These inhibitory effects of the opioid agonists were mostly prevented following coadministration with their respective antagonists. However, naloxone had no significant effect on DHPG levels in any of the hypothalamic regions examined. Plasma LH levels were found to be either low or undetectable in all groups, These results suggest that mu-, kappa- and delta-opioid receptors have inhibitory influence on the hypothalamic noradrenergic neurotransmission around the time of the LH surge. It is thought that the ketamine anaesthesia interfered with LH release. (C) 1999 Elsevier Science Inc.
Keywords: noradrenaline; opioids; HPLC-ECD; ketamine; LH release